When the Kids Move Back Home - Lynda Spence; Larry Forthun (EDIS)
Recent trends show that more and more adult children are returning to live with their parents. With intergenerational cohabitation on the rise, it’s a good idea to examine the “what-ifs” before the doorbell rings. If you find yourself making up spare rooms for your grown children or even their children, you will be glad you thought about the issues in advance. This publication discusses the potential challenges and practical matters you need to know about if your adult children move back home. This 4-page fact sheet was written by Lynda Spence and Larry Forthun and published by the UF Department of Family Youth and Community Sciences, July 2013.